2023
DOI: 10.1002/jgc4.1692
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure and comfort during genetic counseling sessions with LGBTQ+ patients: An updated assessment

Abstract: Disclosure is the act of sharing a stigmatized identity, and members of the LGBTQ+ community make decisions related to disclosure multiple times throughout their life. Disclosure in medical settings can impact perceptions of care and outcomes for LGBTQ+ patients; however, little is understood about the process of decision‐making regarding disclosure in the genetic counseling setting. As such, this study aimed to explore LGBTQ+ experiences in genetic counseling sessions and their disclosure behaviors. Fifty‐fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To limit the minority tax on LGBTQ students, program faculty should intentionally incorporate topics related to LGBTQ identities in their curricula, along with other diversity, equity, and inclusion topics. Genetic counselors have reported desiring more training about LGBTQ topics (Berro et al, 2019;Nathan et al, 2019;Zayhowski et al, 2019) and curricula about being culturally respon- families (Valentine et al, 2023), and genetic counselors should not be assumed to be straight and cisgender, such as was described by participants in this study. Identity topics should not be approached from a deficit model, where people of minoritized groups are viewed as different because their culture or identity is "deficient" compared with those in a majority group (Song & Pyon, 2008).…”
Section: Minority Tax and Lgbtq Studentsmentioning
confidence: 78%
See 4 more Smart Citations
“…To limit the minority tax on LGBTQ students, program faculty should intentionally incorporate topics related to LGBTQ identities in their curricula, along with other diversity, equity, and inclusion topics. Genetic counselors have reported desiring more training about LGBTQ topics (Berro et al, 2019;Nathan et al, 2019;Zayhowski et al, 2019) and curricula about being culturally respon- families (Valentine et al, 2023), and genetic counselors should not be assumed to be straight and cisgender, such as was described by participants in this study. Identity topics should not be approached from a deficit model, where people of minoritized groups are viewed as different because their culture or identity is "deficient" compared with those in a majority group (Song & Pyon, 2008).…”
Section: Minority Tax and Lgbtq Studentsmentioning
confidence: 78%
“…Environments that are not safe or comfortable for identity disclosure can negatively impact LGBTQ students' training. Valentine et al (2023) showed that, from the patient perspective, genetic counselors do not routinely engage in practices that allow for LGBTQ identity disclosure in genetic counseling sessions, despite genetic counselors' reporting that they believe that their patients are comfortable disclosing their identities to them; a similar pattern may apply with students in graduate school. Prior studies have shown that medical students who chose not to disclose their identity to faculty members felt that they were more restricted or inhibited when forming strong relationships with them and lacked mentorship during their programs, creating inequities within the training environment (Dimant et al, 2019; Toman, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations